A multi-omic approach reveals utility of CD45 expression in prognosis and novel target discovery - Ye, Ni; Cai, Jie; Dong, Yulong; Chen, Huiyao; Bo, Zhiyuan; Zhao, Xiaogang; Xia, Mingyang; Han, Mei (Frontiers in Genetics, 2022)
CD45, the leukocyte common antigen, is expressed on almost all cells of the immunological and hematological systems. CD45 expression is related to a variety of diseases, including leukemia and lymphoma. Leukemia can be treated by blocking the function of CD45. However, the role of CD45 across cancers is unclear. In this study, we analyzed the expression level of CD45 across cancers and evaluated the relationship between its expression and patient prognosis. We further integrated genomic and methylation data to explore the differences in CD45 across cancers from a multiomics perspective. We also analyzed the relationship between CD45 expression and levels of immune cell infiltrates and immune modifiers. Our results revealed the distinct expression characteristics and prognostic value of CD45 across multiple tumors. In addition, we screened drug targets based on the immune index defined by CD45 expression and identified that GPR84 affected the proliferation of tumor cells and was associated with the inflammation caused by immunotherapy. In summary, our findings provide a comprehensive understanding of the role of CD45 in oncogenesis and its prognostic significance across cancers.